Age-Related Differences in Head Impact during Experimentally Induced Sideways Falls. (22nd April 2019) - Wood, Tyler A.; Moon, Yaejin; Sun, Ruopeng; Bishnoi, Alka; Sosnoff, Jacob J.
Abstract : Purpose . To examine head impact incidence and head acceleration during experimentally induced falls as a function of age. Methods . 15 young adults (21.2±2.7) and 10 older adults (61.9±4.3 years) underwent 6 experimentally induced sideways falls. Participants fell sideways onto a 20cm crash pad. The number of head impacts was tabulated from video recordings and head acceleration was calculated from motion capture data. A total of 147 falls were analyzed. Results . The young group underwent 88 falls, in which 11.4% resulted in head impact. The older group underwent 59 falls, in which 34.5% resulted in head impact. A proportion analysis revealed older adults had a significantly greater proportion of head impacts than young adults ( X 2 (1) = 11.445, p = 0.001). A two-way ANOVA only revealed a main effect of head impact on acceleration ( F (1, 142) = 54.342, p<0.001). Conclusion . The older adults experienced a greater proportion of head impacts during sideways falls. Head impact resulted in greater head acceleration compared to no head impact. Collectively, this data highlights the possibility that age-related neuromuscular changes to head control may result in elevated risk of fall-related TBIs. Future research examining mechanisms underlying increases in fall-related head impact is warranted.